An Algorithm for Neuropathic Pain Management in Older People - Pickering, Gisèle (Drugs Aging, 2016)
Neuropathic pain frequently affects older people, who generally also have several comorbidities. Elderly patients are often poly-medicated, which increases the risk of drug–drug interactions. These patients, especially those with cognitive problems, may also have restricted communication skills, making pain evaluation difficult and pain treatment challenging. Clinicians and other healthcare providers need a decisional algorithm to optimize the recognition and management of neuropathic pain. We present a decisional algorithm developed by a multidisciplinary group of experts, which focuses on pain assessment and therapeutic options for the management of neuropathic pain, particularly in the elderly. The algorithm involves four main steps: (1) detection, (2) evaluation, (3) treatment, and (4) re-evaluation. The detection of neuropathic pain is an essential step in ensuring successful management. The extent of the impact of the neuropathic pain is then assessed, generally with self-report scales, except in patients with communication difficulties who can be assessed using behavioral scales. The management of neuropathic pain frequently requires combination treatments, and recommended treatments should be prescribed with caution in these elderly patients, taking into consideration their comorbidities and potential drug–drug interactions and adverse events. This algorithm can be used in the management of neuropathic pain in the elderly to ensure timely and adequate treatment by a multidisciplinary team.